A critical enquiry into the psychometric properties of the professional quality of life scale (ProQol-5) instrument - Hemsworth, D.; Baregheh, A.; Aoun, Samar; Kazanjian, A. (W.B. Saunders Co., 2018)
Aim This study had conducted a comprehensive analysis of the psychometric properties of Proqol 5, professional quality of work instrument among nurses and palliative care-workers on the basis of three independent datasets. The goal is to see the general applicability of this instrument across multiple populations. Background Although the Proqol scale has been widely adopted, there are few attempts that have thoroughly analyzed this instrument across multiple datasets using multiple populations. Methods A questionnaire was developed and distributed to palliative care-workers in Canada and Nurses at two hospitals in Australia and Canada, this resulted in 273 datasets from the Australian and 303 datasets from the Canadian nurses and 503 datasets from the Canadian palliative care-workers. A comprehensive psychometric property analysis was conducted including inter-item correlations, tests of reliability, and both convergent and discriminant validity as well as construct validity analyses. In addition, to test for the reverse coding artifacts in the BO scale, exploratory factor analysis was adopted. Results The psychometric property analysis of Proqol 5 was satisfactory for the compassion satisfaction construct. However, there are concerns with respect to the burnout and secondary trauma stress scales and recommendations are made regarding the coding and specific items which should improve the reliability and validity of these scales. Conclusion This research establishes the strengths and weaknesses of the Proqol instrument and demonstrates how it can be improved. Through specific recommendations, the academic community is invited to revise the burnout and secondary traumatic stress scales in an effort to improve Proqol 5 measures.